2007
DOI: 10.1007/s00464-007-9360-3
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing laparoscopic task efficiency: the role of camera and monitor positions

Abstract: Experienced subjects demonstrated superior performance under all study conditions. Optimally, the camera should be directly in front and the monitor should be directly across from a surgeon. Alternatively, the monitor/camera could be placed opposite to the surgeon's non-dominant hand. The suboptimal camera/monitor conditions are especially difficult to overcome for inexperienced subjects. Monitor and camera positioning must be emphasized to ensure optimal laparoscopic performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
61
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 14 publications
3
61
1
Order By: Relevance
“…However, consistent with previous studies that have found optimal performance with the monitor at 0 and significant degradation in performance beyond 45 , 3,12,20 we observed a significant decrease in performance as indexed by MT in the initial trial in the 90 condition. PL (an index of accuracy) and NJ (a marker of fluency/smoothness) demonstrated similar trends but did not reach statistical significance thresholds.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…However, consistent with previous studies that have found optimal performance with the monitor at 0 and significant degradation in performance beyond 45 , 3,12,20 we observed a significant decrease in performance as indexed by MT in the initial trial in the 90 condition. PL (an index of accuracy) and NJ (a marker of fluency/smoothness) demonstrated similar trends but did not reach statistical significance thresholds.…”
Section: Discussionsupporting
confidence: 81%
“…The extant literature has demonstrated (i) performance advantage when the head and hands are pointed in the same direction during visual-motor tasks; (ii) a subjective preference of surgeons for the visual angle to be at 0 ; and (iii) an improved ability in experienced surgeons to deal with rotations of the visual display compared with less experienced surgeons. 11,12 These studies have not quantified the effects of head rotation/viewing angle on visual-motor control processed in MIS and thus the extent to which visual transformations modulate motoric control processes is unclear. Therefore, an empirical investigation into the role of monitor angle on motoric performance in MIS is necessary.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under such conditions, the mirror image of the operative field can disorient the assistant, potentially degrading the performance of their task. Several studies have measured surgical performance under mirror-image conditions in the experimental setting [6][7][8]; however, there are few reports on the extent of difficulties and progressive improvement in performance under reverse alignment conditions in the clinical setting. The present study attempted to examine the learning curve of the assistant during laparoscopic colorectal surgery from the viewpoint of overcoming problems associated with the mirror-imaging effect.…”
mentioning
confidence: 97%
“…In these circumstances, surgeons rely mostly on visual information during the operation. The provided visual information is usually limited [9] and more importantly cannot properly substitute for information regarding compliance, which is best perceived through the sense of touch [10]. For this reason, surgical instruments capable of sensing the mechanical properties of tissue and rendering missing tactile information to the surgeons are needed [6].…”
Section: Introductionmentioning
confidence: 99%